It Ain’t Over Til it’s Over: An Exercise for Concluding a Course - Newman, David (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
We are all aware of the importance of "starting off on the right foot." Probably many of us spend a fair amount of time at the beginning of a course telling our students what will happen and what they will learn. In addition, our syllabi often spell out our specific goals and hopes for the class. Yet after 15 weeks or so, we are likely to let our courses end without so much as a comment. The literature reflects this asymmetry. Much has been written on how to begin a course (establishing rapport, clearly delineating the course objectives, providing a comprehensive syllabus, getting to know one another; see Collins 1986; Dorn 1987; Goldsmid and Wilson 1980), but less attention has been paid to techniques for concluding courses. Furthermore, what has been written tends to be either abstract and advisory in tone (Billson 1986; Goldsmid and Wilson 1980) or peculiar to a specific substantive area (e.g., Phillips 1988; Sherman 1981). This article will provide an excersie for concluding a course.